FARKLI YÖNTEMLERLE KONSERVE EDİLEN KÖRPE MISIR HASILININ KOYUNLARDA RUMİNAL FERMANTASYON VE BESİN MADDELERİNİN SİNDİRİLME DERECESİ ÜZERİNE ETKİSİ - GÜRDOĞAN, FUAT (Fırat Üniveristesi, 1999)
Bu çalışmada, Elazığ'da tahıl haşatından sonra, ikinci ürün olarak silajlık mısırın yetiştirilme olanağı ile birlikte, iklim koşullan nedeniyle körpeyken biçilmek zorunda kalınan silajlık mısır hasılının, farklı yöntemlerle konserve edilmesinin silaj kalitesi, ruminal fermantasyon ve ham besin maddelerinin sindirilme derecesi üzerine etkisi incelenmiştir. Araştırma, 6x6 Latin Kare Deneme Düzeninde ve 6 aylık aynı canlı ağırlıkta 6 baş İvesi ırkı erkek toklu üzerinde yürütülmüştür. Araştırma grupları ise, konserve yöntemlerine göre belirlenmiştir. Buna göre, biçildiği gün yaş olarak silolanan Y grubunu, 24-48 saat toprak üsütünde pörsütülerek silolanan Pt grubunu, 24-48 saat çatı altında pörsütülerek silolanan Pç grubunu, HC1 ile işlenmiş samanla karılarak (%20 saman + %80 yaş hasıl) silolanan Y+S grubunu, toprak üstünde kurutulan Kt grubunu ve çatı altında kurutulan Kç grubunu oluşturmuştur. Silo materyallerine göre tüm silaj gruplarında ham kül, ham selüloz, acid detergent fiber ve ham yağ düzeyleri yükselmiş, kuru madde, organik madde, ham protein, neutral detergent fiber ve azotsuz öz madde düzeyleri de düşmüştür. Fermantasyon ürünlerinden laktik asit düzeyi Y+S grubunda, NH3-N düzeyi ise Y grubunda daha yüksek bulunmuştur. Beta-Karoten düzeylerinde, taze materyallerine göre, tüm gruplarda bir düşme meydana gelirken, bu düşüş en fazla olarak Kt grubunda ve en az olarak da Y grubunda gerçekleşmiştir. Rumen sıvısının pH'sı, her üç ölçümde de, kuru ot gruplarında silaj gruplarına göre yüksek çıkmış, en düşük değer de, Y+S grubunda saptanmıştır (p<0.05). NH3 konsantrasyonu ise, en yüksek değere Y grubunda ulaşmış (p<0.05), diğer gruplar arasında pek fark görülmemiştir. Toplam uçucu yağ asidi, asetik asit, propiyonik asit ve butirik asit konsantrasyonu, kuru ot gruplarında silaj gruplarından daha düşük bulunurken (p<0.05), silaj gruplarındaki en düşük değerler ise, butirik asit hariç, Y grubunda tespit edilmiştir (p<0.05). Kuru madde, ham kül, organik madde, ham selüloz, ham protein, ham yağ ve azotsuz öz maddenin sindirilme dereceleri, en yüksek değere çatı altında porsutulmuş materyalle yapılmış silaj grubunda ulaşırken, bunu Y+S ve Pt grupları izlemiştir (p

In this trial, the feasibility of producing whole corn as a second crop after cereal harvest and the effects of different conservation methods of whole crop corn harvested at boot stage because of the necessity of climatic conditions in Elazığ on silage quality, ruminal fermantation and digestibility of nutrients were investigated. The study was conducted using 6x6 Latin Square trial in 6 Ivesi lambs at the age of 6 months and the same weights. The study groups were formed according to the conservation methods applied to the feed material. In this respect, Y group ensiled as fresh on the same day of harvesting, Pt group ensiled after wilting 24-48 h on the ground, Pç group ensiled after wilting 24-48 h under a roof, Y+S group, ensiled as fresh by adding straw treated with HC1 (fresh material 80% + straw 20%), Kt group dried on the ground and Kç group dried under a roof. Ash, crude fiber, acid detergent fiber and eter extract contents increased in silage groups when compared with fresh materials. In contrast, dry matter, organic matter, crude protein, neutral detergent fiber and nitrogen free extract contents decreased. Lactate concentration was higher in Y+S group and NH3-N concentration was higher in Y group. Beta-Karoten contents decreased in all groups when compared with fresh materials but the greatest decrease was obtained in Kt group and the least was in Y group. The pH levels of rumen liquid in dried groups were higher than the silage groups in 1, 3, and 5 h measurements and the lowest pH level was obtained in Y+S group (p<0.05). The highest level of NH3 concentration was determined in Y group (p<0.05) and the differences between the other groups were not statistically significant. The concentrations of total volatty acids, acetate, propionate and butyrate were found to be lower in dried groups than silage groups (p<0.05) and the lowest values were obtained in Y group, except for butyrate concentration (p<0.05). The highest digestibility of dry matter, ash, organic matter, crude fiber, crude protein, eter extract and nitrogen free extract was found to be in Pç group and this was followed by Y+S and Pt groups (p<0.05). The lowest digestibility of nutrients was detected in Kt group (p<0.05). It was suggested and statistically prooved that (p<0.05), ensiling the whole crop corn harvested at boot stage either by wilting under a roof or in the absence of wilting conditions adding straw treated with HC1 so as to increase the level of dry matter and to37 decrease the environment's pH level and also, drying this whole crop corn under a roof when compared with drying on the ground have better effects on feed quality, ruminal fermantation products and digestibility of nutrients.
The Effect of whole crop corn conserved with different methods on ruminal fermantation and digestibility of nutrients in sheep
Keywords: Veteriner Hekimliği; Veterinary Medicine